2022
DOI: 10.1155/2022/9347172
|View full text |Cite
|
Sign up to set email alerts
|

Italian Version of the Internet Self-Efficacy Scale: Internal and External Validation

Abstract: Online activities are a fundamental part of daily life in this digital era and Internet self-efficacy (ISE) became a central construct for the psychologists of virtual environments. The Internet Self-Efficacy Scale developed by Kim and Glassman (2013) is a recent, valid, and reliable 17-item test to assess the ISE. The aim of this research, composed by two studies, was to translate and validate the Italian version of the ISS. In study 1, we evaluated the factorial validity and internal consistency of the Itali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 82 publications
1
5
0
Order By: Relevance
“…A few items on the scale are "I can use the Internet to answer other people's questions in a productive way," and "I can use the Internet to answer my own questions in a productive way." The previous studies have reported the internal consistency of the five subscales in the range of 0.72-0.91, and for the overall scale, CA ranged from 0.91 to 0.95 (Guazzini et al, 2022;_ Izzettin et al, 2019;Kahraman and Yilmaz, 2018). In this study, CA values for each subscale were 0.75, 0.71, 0.82, 0.74, 0.86 and the internal consistency for the entire scale was reported as 0.88.…”
Section: Data Collection and Participantssupporting
confidence: 47%
See 1 more Smart Citation
“…A few items on the scale are "I can use the Internet to answer other people's questions in a productive way," and "I can use the Internet to answer my own questions in a productive way." The previous studies have reported the internal consistency of the five subscales in the range of 0.72-0.91, and for the overall scale, CA ranged from 0.91 to 0.95 (Guazzini et al, 2022;_ Izzettin et al, 2019;Kahraman and Yilmaz, 2018). In this study, CA values for each subscale were 0.75, 0.71, 0.82, 0.74, 0.86 and the internal consistency for the entire scale was reported as 0.88.…”
Section: Data Collection and Participantssupporting
confidence: 47%
“…Further, these subscales are grouped into three levels of self-efficacy. A few items on the scale are “I can use the Internet to answer other people’s questions in a productive way,” and “I can use the Internet to answer my own questions in a productive way.” The previous studies have reported the internal consistency of the five subscales in the range of 0.72–0.91, and for the overall scale, CA ranged from 0.91 to 0.95 (Guazzini et al. , 2022; İzzettin et al.…”
Section: Study 2: Reliability and Validity Testingmentioning
confidence: 98%
“…Therefore, it seems clear that there is a need to continue working on measurement tools focusing on the levels of self-confidence according to gender to design initiatives to develop the digital competence of women workers. As Guzzani et al [65] point out, depending on the tool used, the results show a greater or lesser gender digital divide, and in the case of online tasks, no significant results are obtained.…”
Section: Lack Of Data On Gender Differences In Relation Tomentioning
confidence: 88%
“…Self-efficacy is characterized by commitment to goals, application of learning habits, and learning method adaptation [33]. It is important to note that self-efficacy is not a skill but a belief in an individual's ability [34], and it directly affects internet confidence [35]. This simply means that healthy self-efficacy is able to improve the student's confidence in using the internet.…”
Section: Discussionmentioning
confidence: 99%